2009
DOI: 10.3390/md7030367
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bioactive Oxylipins from Marine Diatoms on Invertebrate Reproduction and Development

Abstract: Diatoms are one of the main primary producers in aquatic ecosystems and occupy a vital link in the transfer of photosynthetically-fixed carbon through aquatic food webs. Diatoms produce an array of biologically-active metabolites, many of which have been attributed as a form of chemical defence and may offer potential as candidate marine drugs. Of considerable interest are molecules belonging to the oxylipin family which are broadly disruptive to reproductive and developmental processes. The range of reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 181 publications
2
94
0
1
Order By: Relevance
“…Studies on bioactive aldehydes have showed that these compounds may inhibit the growth of different marine invertebrates such as diatom predators and induce different responses in marine ecosystem (Caldwell, 2009;Lauritano et al, 2016). This property may explain the dynamics behind some blooms and also explain why oxylipin profiles can be used as an additional taxonomic identification tool, providing a functional feature to species characterization and morphological traits.…”
Section: Oxylipinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on bioactive aldehydes have showed that these compounds may inhibit the growth of different marine invertebrates such as diatom predators and induce different responses in marine ecosystem (Caldwell, 2009;Lauritano et al, 2016). This property may explain the dynamics behind some blooms and also explain why oxylipin profiles can be used as an additional taxonomic identification tool, providing a functional feature to species characterization and morphological traits.…”
Section: Oxylipinsmentioning
confidence: 99%
“…d (Volkman et al, 1998;Viegelmann et al, 2014). e (Paul and Fenical, 1986;Nappez et al, 1996;Girona et al, 1997;Caldwell, 2009;Lauritano et al, 2016).…”
Section: Lipids and Fatty Acids In Diatomsmentioning
confidence: 99%
“…Unsaturated fatty acid oxidative products, oxylipins [46], are cytotoxic for bacteria, fungi, algae, molluscs, crustaceans, and echinoderms [47], suppressing growth and reproduction [48][49][50]. Oxylipin production in diatoms is wound-activated as would occur during predation and affects population dynamics of copepods [50].…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Reactions with membranes are one of the most prevalent mechanisms of cellular injury and comparisons in warm and cold environments are particularly interesting because of differences in oxygen solubility and conductance in tissues [43] as well as in membrane unsaturation and rates of reactive oxygen species production and lipid peroxidation [45]. Unsaturated fatty acid oxidative products, oxylipins [46], are cytotoxic for bacteria, fungi, algae, molluscs, crustaceans, and echinoderms [47], suppressing growth and reproduction [48][49][50]. Oxylipin production in diatoms is wound-activated as would occur during predation and affects population dynamics of copepods [50].…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Diatoms are one of the main primary producers in aquatic ecosystems. They are considered to be passive participants in energy transfer in the food webs, being heavily grazed by their predators and exhibiting little or no anti-grazing capacity [26]. A number of diatom species produce the potent neurotoxin domoic acid, including Pseudonitzschia, Nitzschia, and Amphora [10].…”
Section: Discussionmentioning
confidence: 99%